Evaluating the migration of boundary river shorelines and coastal land cover changes for the Beilun River between China and Vietnam - Xie Shuangmi; Zhang Wenzhu; Wu Bin; Lu Shengquan; Gu Guanhai; Liu Yanhua (Journal of Hydrology: Regional Studies)
Study region: The China-Vietnam Beilun River Study focus: Reconstruction of the historical river course of the Beilun River along the China–Vietnam border using multi-source data and application of the DSAS model to describe the changes and characteristics of different river segments; Quantification of land cover changes and characteristics along the Beilun River coastline using land dynamics and land transfer matrices; Analysis of the impact of river shoreline changes on land cover changes on both banks by overlaying shoreline change maps with land cover change maps. New hydrological insights for the region: Both banks of the boundary river tend to shift towards the opposite side, but the overall trend is a shift towards the Chinese side. The Chinese bank is characterized by erosion, while the Vietnamese bank is dominated by accretion. The Beilun River floodplain comprises more than 70 % cultivated land and forest land. Analysis of dynamic degree and transfer matrices shows a contraction of cultivated land, forest land, and water bodies, with a significant increase in construction land and other types of land, reflecting a conversion between cultivated and forest land and the encroachment of construction land on cultivated land. The migration of the boundary river shoreline has significantly impacted land cover. To address transboundary resource management issues, it is recommended that China and Vietnam sign a treaty with international legal validity.